Effects of Ramadan Fasting on Intradialytic Hypoglycemia and Clinical Outcomes in Patients with Diabetes on Maintenance Hemodialysis: A Multicenter Prospective Cohort Study in Southern Thailand - Ashari Saman; Jayanton Patumanond; Moragot Chatatikun; Atthaphong Phongphithakchai (Medical Sciences, 2026)
Background: Patients with end-stage kidney disease (ESKD) and diabetes undergoing maintenance hemodialysis (HD) may be at increased risk of metabolic disturbances and intradialytic complications during Ramadan fasting. However, evidence regarding the safety of fasting in this population remains limited. This study evaluated the association between Ramadan fasting and intradialytic hypoglycemia and other clinical outcomes. Methods: This multicenter prospective cohort study included 153 patients with ESKD and diabetes undergoing maintenance HD at four centers in Thailand during the pre-Ramadan and Ramadan periods in 2024. Participants were categorized as non-fasting, partial fasting, or full fasting. All underwent HD using glucose-containing dialysate (100 mg/dL) and received standardized pre-Ramadan medication adjustments, including insulin dose reduction and oral glucose-lowering medication modification. The primary outcome was intradialytic hypoglycemia, defined as a blood glucose level